Environmental impacts and nitrogen-carbon-energy nexus of vegetable production in subtropical plateau lake basins - He, Yousheng; Su, Ruifeng; Wang, Yuan; Li, Shunjin; Huang, Qi; Chen, Xinping; Zhang, Wei; Yao, Zhi (Frontiers in Plant Science, 2024)
Vegetables are important economic crops globally, and their production has approximately doubled over the past 20 years. Globally, vegetables account for 13% of the harvested area but consume 25% of the fertilizer, leading to serious environmental impacts. However, the quantitative evaluation of vegetable production systems in subtropical plateau lake basins and the establishment of optimal management practices to further reduce environmental risks are still lacking. Using the life cycle assessment method, this study quantified the global warming, eutrophication, acidification, and energy depletion potential of vegetable production in a subtropical plateau lake basin in China based on data from 183 farmer surveys. Our results indicated that vegetable production in the study area, the Erhai Lake Basin, was high but came at a high environmental cost, mainly due to low fertilizer efficiency and high nutrient loss. Root vegetables have relatively high environmental costs due to the significant environmental impacts of fertilizer production, transportation, and application. A comprehensive analysis showed that the vegetable production in this region exhibited low economic and net ecosystem economic benefits, with ranges of 7.88-8.91 × 10 3 and 7.35-8.69 × 10 3 $ ha -1 , respectively. Scenario analysis showed that adopting strategies that comprehensively consider soil, crop, and nutrient conditions for vegetable production can reduce environmental costs (with reductions in global warming potential (GWP), eutrophication potential (EP), acidification potential (AP), and energy depletion potential (EDP) by 10. 6-28.2%, 65.1-73.5%, 64.5-71.9%, 47.8-70.4%, respectively) compared with the current practices of farmers. This study highlighted the importance of optimizing nutrient management in vegetable production based on farmers' practices, which can achieve more yield with less environmental impacts and thereby avoid the "trade-off" effect between productivity and environmental sustainability.